2021
DOI: 10.1088/1742-6596/1874/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

Unwinding Environment in the Lecture Room Using Mobile Learning (M-Learning) Adoption among the Millennial Generation

Abstract: Information and Communication Technology (ICT) has provided flexibility for teachers and students to engage in academic discourse irrespective of the location. With rapid technological advancements, Mobile learning offers incredible opportunities, especially in higher education especially during this Covid-19 pandemic. The advancement of mobile and wireless communication technologies has encouraged the mobile learning method where students are able to learn via mobile devices without being limited by space and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
2
2
0
Order By: Relevance
“…Based on the findings, the present study concluded that providing high ITI specifications would lead to greater acceptance of M-learning among students. This finding is consistent with prior studies [66,67].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Based on the findings, the present study concluded that providing high ITI specifications would lead to greater acceptance of M-learning among students. This finding is consistent with prior studies [66,67].…”
Section: Discussionsupporting
confidence: 94%
“…Saudi universities have high levels of management capabilities that could help in implementing M-learning systems successfully. Our findings are consistent with those of prior studies [66,67]. The present study concluded that university management support is one of the most significant factors influencing the acceptance of M-learning among students in Saudi universities.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to several studies in the information system context, identifying quality factors is a critical step for guaranteeing the successful implementation of any new system [48][49][50][51][52]. Other studies confirmed the positive and significant role of quality factors in enhancing the usage of many types of information systems among users [53][54][55]. Based on that, the main quality measurements for mobile learning applications should be properly identified [56], and quality requirements should be correctly understood by mobile learning application developers and designers from the beginning stage of the development.…”
Section: Literature Review and Research Backgroundmentioning
confidence: 99%